Respuesta :
Answer:
D. 5x + 5
Step-by-step explanation:
(9x2 + 10x + 4) − (9x2 + 5x − 1) =
Remove the first set of parentheses since they are unnecessary.
To remove the second set of parentheses, change every sign inside.
= 9x2 + 10x + 4 − 9x2 - 5x + 1
Combine like terms.
= 5x + 5
Answer: D. 5x + 5
The simplified form of this expression (9x2 + 10x + 4) − (9x2 + 5x − 1) is 5x+5 option (D) is correct.
What is a quadratic equation ?
Any equation of the form [tex]\rm ax^2 +bx+c= 0[/tex] Where x is variable and a, b, and c are any real numbers where a ≠ 0 is called a quadratic equation.
[tex]=\rm (9x^2 + 10x + 4) - (9x^2 + 5x- 1)[/tex]
[tex]=\rm 9x^2 + 10x + 4 - 9x^2 - 5x+ 1)\\\\= 5x+5[/tex]
Thus, the simplified form of this expression (9x2 + 10x + 4) − (9x2 + 5x − 1) is 5x+5 option (D) is correct.
Learn more about quadratic equations here:
brainly.com/question/2263981
#SPJ2